Molecular analyses of Salvia Africana-Lutea L. transgenic hairy root clones for secondary bioactives - Ramogola, Watsie Princess Neo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2009.